Aspirin, Clopidogrel and Gastrointestinal Hemorrhage: What is the Evidence? - Ferreira-Alves , Eduarda; Lamas, Joana; Rocha-Cruz, Mariana (Gazeta Médica, 2022)
INTRODUCTION: The acetylsalicylic acid (ASA), frequently designated as aspirin, is widely used in the secondary prevention of cardiovascular events. Clopidogrel is another platelet antiaggregant used with the same purpose. It is well known the association between ASA and an increased risk of gastrointestinal (GI) complications. On the other hand, there is some evidence that suggests a reduction of this risk using clopidogrel, in comparison to ASA. As a result, it is common the substitution of ASA for clopidogrel in bleeding related situations. Our aim was to evaluate if clopidogrel is superior in the reduction of GI bleeding risk in patients with secondary cardiovascular prevention comparing with ASA. METHODS: A research was carried out of all the articles published between January of 2000 and August of 2020, in English and Portuguese language and indexed in PubMed, Cochrane, DARE, National Guideline Clearinghouse, Canadian Medical Association Practic Guidelines Infobase and Evidence Based Medicine Online. The MeSH terms used were “Clopidogrel”, “Aspirin” and “Gastrointestinal hemorrhage”. The levels of evidence and strength of recommendation attributed were based in the Strength of Recommendation Taxonomy (SORT). RESULTS: Initial research found 278 articles. Ten were included in this review: one systematic review, four randomized clinical studies, three cohort retrospective studies, one cohort prospective study and one prospective case-control study. CONCLUSION: Studies with higher quality of evidence point to the non-superiority of clopidogrel in comparison with ASA about the risk of GI complications (SORT B). Other studies suggest that the use of ASA associated with proton-pump inhibitors reduces the risk in comparison to clopidogrel alone. Since there is no consensus between different studies, we suggest that new ones should be carried out, targeting specifically this topic, ideally randomized clinical trials.